Karakter Game Berbasis Tokoh Raut Golek Sunda - Donny Trihandono; Irfansyah Irfansyah (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2010)
This article is a note from the research concerning on bringing character traits and visual forms of Sundanese golek puppetry into game character. The distinctive side of golek puppetry itself is located in its measurement for the relation between the personality of a character and its visual appearance. This makes golek puppetry as an entertainment with spirit. This research itself is a basis for development of game character (research and development). The conclusions derived from this research used as bases for character development, therefore creating a new and distinctive work. Moreover, this research is equipped with preliminary data-collection and narratives about golek and characters derived from literatures and interviews. A result from this research is a new kind of characters that have its distinctive side compared to usual characters in the gaming world. Uniqueness is come out from the distinctive side of golek puppetry in performing visual form that's match with the personality of the characters performed.